2006
DOI: 10.1002/hlca.200690211
|View full text |Cite
|
Sign up to set email alerts
|

Quenching of Singlet Oxygen by Tertiary Aliphatic Amines. Structural Effects on Rates and Products

Abstract: In memoriam Professor Hanns FischerA kinetic and product study of the reaction of a series of a-methyl-substituted N-methylpiperidines with thermally generated 1 O 2 in MeCN was carried out. It was found that as the number of a-methyl groups (Me in a-position relative to the N-atom) increases, the rate of 1 O 2 quenching (physical plus chemical) slightly decreases. This finding shows that, with respect to the reaction rate, steric effects are much more important than electronic effects as the latter should hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
1
15
1
Order By: Relevance
“…Alternatively, adsorbed O 2 captures hot electron to form very reactive anionic oxygen that readily extracts protons from the organic molecules or water to generate more reactive free radical species to initiate the oxidation reaction. , Furthermore, recent experimental observations indicate that plasmonic nanoparticles enhance the efficiency of photosensitizers to generate singlet oxygen. Considering that MB is a well-known photosensitizer, the photochemical N-demethylation is likely to involve singlet oxygen. In fact, it has been shown that singlet oxygen drives N-demethylation of different organic molecules. …”
Section: Plasmon-pumped Adsorbate Excitation and Photochemistrymentioning
confidence: 99%
“…Alternatively, adsorbed O 2 captures hot electron to form very reactive anionic oxygen that readily extracts protons from the organic molecules or water to generate more reactive free radical species to initiate the oxidation reaction. , Furthermore, recent experimental observations indicate that plasmonic nanoparticles enhance the efficiency of photosensitizers to generate singlet oxygen. Considering that MB is a well-known photosensitizer, the photochemical N-demethylation is likely to involve singlet oxygen. In fact, it has been shown that singlet oxygen drives N-demethylation of different organic molecules. …”
Section: Plasmon-pumped Adsorbate Excitation and Photochemistrymentioning
confidence: 99%
“…•− , 52 and 1,4diazobicyclo(2,2,2)-octane)DABCO) to quench 1 O 2 53 (Figure 3C). To determine which ROS species were involved in the signal transduction via enzymatic reaction, we repeated the ROS fluorescence measurement of the tyrosinase−dopamine reaction in the presence of ROS scavenging agents (Figure 3D).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To investigate the hypothesis that ROS caused the TYR–CNT response, we generated several ROS species in the presence of the DNA–CNT complexes via the copper Fenton reaction (Figure C). We also made use of mannitol to quench • OH, (2,2,6,6-tetramethylpiperidin-1-yl)­oxyl or (2,2,6,6-tetramethylpiperidin-1-yl)­oxidanyl)­TEMPO to trap O 2 •– , and 1,4-diazobicyclo­(2,2,2)-octane)­DABCO) to quench 1 O 2 (Figure C). To determine which ROS species were involved in the signal transduction via enzymatic reaction, we repeated the ROS fluorescence measurement of the tyrosinase–dopamine reaction in the presence of ROS scavenging agents (Figure D).…”
Section: Results and Discussionmentioning
confidence: 99%
“… *The corresponding values for 2‐methoxyphenothiazine are: λ max [log ε ]: 214 [4.5], 252 [4.5], 316 [3.6]; † Phenothiazine was used as the reference compound ( λ exc = 334 nm, ϕ F = 0.0034 in MeOH or ethanol) ; ‡ This value was calculated using PIND as the triplet acceptor [ λ max = 380 nm, ε T = 31000 m −1 cm −1 , E T = 51.2 kcal/mol , k q = (1.8 ± 0.1) × 1010 m −1 s −1 ]. The reported value for N ‐methylphenothiazine in HX is 23000 m −1 cm −1 and 27000 m −1 cm −1 for phenothiazine in MeOH ; § The triplet energy was calculated with the phosphorescence emission in ethanol glass under the following conditions: A 311 = 0.32 (path‐length = 1 cm), emission and excitation slits set at 5 nm, maximum wavelength = 475 nm; ∥ The reported value for 2‐methoxyphenothiazine is 6 × 109 m −1 s −1 ; ¶ Photophysical properties were measured in a solution of LPZ‐MS.…”
Section: Resultsmentioning
confidence: 99%
“…In deuterated MeOH, on the other hand, the corresponding rate constants are 7.28 × 10 7 , 3.79 × 10 7 and 1.63 × 10 7 m −1 s −1 . The differences in these rate constants are predictable because free CPZ has a terminal amine with nonbonding electrons capable of interacting with singlet oxygen . Furthermore, the singlet oxygen quenching constant of phenothiazine is larger than its sulfoxide formation constant .…”
Section: Introductionmentioning
confidence: 99%